Environmental evaluation of two alternative road alignments to the Mohale dam (phase 1B of LHWP) - Hughes, Jessica Jane (Department of Environmental and Geographical Science, 2024)
Construction of the Mohale Dam (Phase lB) of the Lesotho Highlands Water Project (LHWP) requires a reliable and economic access road for transporting construction materials from the Lesotho-South Africa border. Dam construction is due to begin in 1996. It is at this stage unknown whether the dam wall will be a rockfill or concrete arch; the choice will influence the type and volume of material to be transported. The Lesotho Highlands Development Authority (LHDA) will be responsible for construction and maintenance of the road during dam construction (five years). Thereafter, responsibility for the maintenance of the road reverts to the Roads Department of the Government of Lesotho. The Lesotho Highlands Development Authority (LHDA) awarded Contract 1000 to the Gibbs-Bergman Joint Venture (GBJV) in December 1992. The Environmental . Evaluation Unit (EEU) at the University of Cape Town (UCT) was subsequently contracted by GBJV to conduct an environmental impact assessment of alternative road alignments with the specific brief of investigating biophysical, social and compensation aspects. Impacts associated with dam construction were not included in the terms of reference. The flow diagram in Figure 1 illustrates the role of the various consultants involved in the project, and the phasing of the project components.